Wheel-spinning in a game-based learning environment for physics - Palaoag, Thelma D (Archīum Ateneo, 2016)
We study wheel-spinning behavior among students using an educational game for physics. We attempted to determine whether students wheel-spin, and to build a wheel-spinning detector. We found that about 30 to 40 % of students are unable to successfully complete a level when attempting it 8 times or more, or when working on it for more than 160 s. We also found that past performance is predictive of wheel-spinning, and that persistence increases both the likelihood of success and of wheel-spinning. Finally, we found that wheel-spinning in this context is different from wheel-spinning exhibited in prior work in that it is relatively easy to detect and does not suffer from cold starts.